Does the Direction of Kinesiology Tape Application Influence Muscle Activation in Asymptomatic Individuals? - Michelle Dolphin; Gary Brooks; Blair Calancie; Adam Rufa (North American Sports Medicine Institute, 2021)
# Background Despite the popularity of tape among athletes and rehabilitation practitioners, there is controversy regarding the specific effects of kinesiology tape. Based on conflicting results and limitations of the literature, a well-designed study was desired to examine kinesiology tape application direction on muscle activation. # Hypothesis/Purpose The purpose of this pilot study was to determine if the direction of kinesiology tape application influences quadriceps activation. This study compared taping techniques with outcome measures selected to assess quadriceps muscle activation. The outcome measures included EMG, isokinetic strength, and functional hop and jump performance. # Study Design Double-blind Crossover study # Methods A total of fifteen asymptomatic participants (10 females and 5 males) completed the study. Mean age was 23.3 years. Kinesio^Ⓡ^ Tex Gold^TM^ was applied to the dominant lower extremity of each participant using a Y-strip method. Two taping conditions (proximal to distal, distal to proximal) were applied to the quadriceps. Participants and testers were blinded to tape condition. Pretest and posttest measures included electromyographic output during isokinetic testing of quadriceps muscle torque at 60°s^-1^ and 120°s^-1^, single leg triple hop for distance, and vertical jump. # Results Two-way, repeated measures analysis of variance resulted in no significant differences in baseline to taped condition for quadriceps electromyographic output, quadriceps isokinetic knee extension muscle torque at 60°s^-1^ and 120°s^-1^, single leg triple-hop distance or vertical jump height. # Conclusion The results of this pilot study do not support the hypothesis that kinesiology tape application direction influences muscle performance as measured in this study. # Levels of Evidence Level 1 - Controlled Clinical Trial # Clinical Relevance Kinesiology tape is commonly used as an intervention for a wide range of musculoskeletal conditions and for promoting performance including sporting activities. Kinesiology tape is popular among athletes and health care providers yet the specific effects of tape are not well understood.